«Intended to prepare a march replenishment for active Red Army»: to the history and perpetuation of memory of 39th Omsk reserve rifle brigade (division) - A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the reconstruction of the history of the 39th Omsk reserve rifle brigade (division). Attention is focused to the contribution of the Omsk military unit to the Great Victory. The article proved that during the years of World War II, the brigade sent to the front the largest number of fighters in comparison with other units formed in the Omsk region and sent to the front in full force. Thanks to the courage and heroism of the soldiers and officers trained in Omsk, the notable contribution of the soldiers who arrived to the front from Siberia in the victory over fascism, the country’s leadership was given the honorary name Omsk. Based on the above information on the history of the 39th Omsk reserve rifle brigade, the author comes to the conclusion that it is necessary to perpetuate her memory in Omsk, and in particular at Omsk memorials